Building Credible VTOL Flight Models for Handling Quality Certification by Simulation - Lorenzo Favaro; Agata Rylko; Giuseppe Quaranta (Aerospace)
Certifying novel VTOL aircraft handling qualities (HQs) may be challenging, relying on costly and high-risk flight testing. This paper presents a methodology to establish the credibility of flight simulation models for certification by simulation, aiming to bridge the gap between the model input uncertainty and certification confidence. The core objective is to assess if a model, despite its inherent uncertainties, can reliably predict the handling quality compliance for specific flight tasks. This is achieved by quantifying the impact of input parameter uncertainties on predicted handling qualities and, crucially, by evaluating the envelope of the resulting uncertain aircraft transfer functions—scaled by a confidence ratio—against established maximum unnoticeable added dynamics boundaries. Applied to a lift + cruise VTOL model performing a deceleration-to-hover manoeuvre, the study demonstrates that while longitudinal control dynamics largely remained within MUAD limits, indicating the model’s credibility for those aspects, vertical axis dynamics coupled with longitudinal inputs for some uncertain configurations exceeded these limits, correlating with observed flight test performance variability. Readers will find a structured, quantitative approach to model validation for HQ certification by simulation, leveraging MUAD to determine if a nominal model is sufficiently representative for certification, thereby supporting safer and more efficient VTOL development.